GROWTH RESPONSES OF FIVE NON TOXIC ALEXANDRIUM SPECIES (DINOPHYCEAE) TO TEMPERATURE AND SALINITY - Lim, Po-Teen; Leaw, Chui-Pin; Kaga, Shinnosuke; Sekiguchi, Katsushi; Ogata, Takehiko (Marine Research in Indonesia, 2007)
Growth response of five clonal cultures of Alexandrium obtained from tropical and temperate waters were examined. Experiments were carried out in eighteen variable temperature-salinity conditions (temperatures of 15 Â°C, 20Â°C, and 25Â°C; salinities between 5 to 30 psu) under constant illumination of 150 Â± 10.0 Amol m-2 s- at 15:9 light:dark photo-cycle. Our results showed optimum growth of all Alexandrium species at 20 - 25Â°C. The salinity range for optimum growth however varied among the species. Growth rates of A. eine, A. insuetum, and A. fraterculus (0.28 â 0.37 day) were higher than those of A. leei and A. pseudogoniaulax under the same culture conditions (0.14 â0.22 day-). The three temperate species showed positive growth at suboptimum temperature, 15Â°C, but the tropical species did not grow and died off. Salinity tolerance of the five species in decreasing order was A. pseudogoniaulax > A. leei > A. insuetum > A. affine > A. fraterculus. Results of the present study showed vast variations in salinity tolerance among the Alexandrium species regardless the geographical origins. Adaptation of the temperate species at higher temperature indicated that the species might proliferate in warm tropical waters.